Model of Behavior in Improving Academic Resilience in Nursing Students - GRATSIA VICTORIA FERNANDEZ; Theodehild Maria Theresia Dee; Maria Lupita Nena Meo (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2024)
Introduction: Academic resilience was identified as a means of overcoming the educational and practical challenges nursing students face. Information on increasing academic resilience in nursing students has not been widely studied. Therefore, the relationship between academic resilience and other constructs must be assessed to propose an appropriate approach. This study aimed to determine the behavioral model for increasing the academic resilience of nursing students.Method: The research method used is a cross-sectional quantitative research method. The population in this study consisted of nursing students at two nursing education institutions in Indonesia, with as many as 300 respondents who were taken using the Proportionate Stratified Random Sampling technique. The instruments used in this research are The Academic Resilience Scale-24, Self-Compassion Scale Short Form, Perfectionism Scale, and Perception Of Academic Stress Scale. Data analysis using Partial Least Square.Results: The behavioral model in increasing the academic resilience of nursing students is formed from self-compassion, perfectionism, and academic stress with a T statistics value> 1.96 and a p-value <0.05.Conclusions: Self-compassion (consisting of Self-Kindness, Self-Judgment, Common Humanity, Isolation, Mindfulness, and Over-identified), Perfectionism (consisting of Self-Oriented Perfectionism, Other-Oriented Perfectionism, and Socially Prescribed Perfectionism), and academic stress (consisting of from academic expectations, assignments and exams, and students' academic self-perception) can directly affect academic resilience (consisting of Perserverance, Reflecting and Adaptive Help-seeking and Negative Affect and Emotional Response). Furthermore, self-compassion can indirectly affect academic resilience through the mediation of perfectionism and academic stress.